IMPLEMENTATION OF THE MOZAIK METHOD TO RECOGNIZE VOCAL LETTERS IN LITTLE DISABILITY CHILDREN - Milatul Zulfa (Sunan Kalijaga International Journal on Islamic Educational Research, 2020)
This study aims to determine the implementation process or the application of the mosaic method in introducing vowels for mild retarded children who are in grade 1 at Giwangan Elementary School in Yogyakarta. In addition, this study also aims to determine the changes that occur in mild retarded students after using the mosaic method in learning Indonesian, specifically to introduce vowels. This research uses qualitative methods with descriptive qualitative research. The subjects in this study were grade 1 students with intellectual disabilities who had the initials X at Giwangan Elementary School in Yogyakarta. The object of this research is the application of the mosaic method as a solution to introduce vowels in mildly retarded children. Data collection techniques such as observation, interviews, documentation, and field notes. The results of this study indicate that by using the mosaic method in learning the introduction of vowels in mild retarded children is actually feeling very enthusiastic and have a spirit of learning rather than by using methods that have been previously applied. In addition, with mild mental retardation X, was very happy and painstaking with little by little sticking pieces of paper that were pasted and arranged to be a letter in question.